PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KUE BASAH TRADISIONAL PADA USAHA MIKRO CI ALIH SUKAJADI KOTA BOGOR - Benny Osta Nababan; Wawan Hari Subagyo; Dwi Oktiana Irawati; Andri Budi Susanto; Shofie Salsabila Kalmindah (Institut Teknologi dan Bisnis Dewantara, 2024)
This research aims to determine consumer purchasing decisions for traditional wet cakes at the Cialih Sukajadi micro-enterprise, Bogor City. Research data collection was carried out using a digital questionnaire technique, namely through a closed Google Form which was distributed to 100 respondents who were shown to consumers of Cialih Sukajadi and its surroundings. (1) The results of the F test research show that the independent variables (product, price, promotion and location) have a significant effect simultaneously on the dependent variable (purchasing decision), seen from the significant value below 0.1 and the calculated F value 13.788 > F table 2, 00. (2) As well as the results of the t-test calculation, where the location variable obtained a t-count of 3.491, so it can be said that the location variable is the variable that most influences the purchasing decision variable for traditional Cialih Sukajadi wet cakes, Bogor City. (3) The coefficient of determination (adjusted R) is 0.341, which means that the marketing mix can be explained by a model with independent variables (product, price, promotion and location) of 34.1% while the remaining 65.9% is explained by other factors outside the variables. researched.